塩化亜鉛配合の液体歯磨ハイザックNリンスの口臭抑制効果 - 中村 幸香; 八島 章博; 角田 衣理加; Yamamoto Ken; 吉野 陽子; 鶴本 明久; 前田 伸子; 中川 洋一 (ORAL THERAPEUTICS AND PHARMACOLOGY, 2017)
[Purpose] The purpose of this study was to clarify the effectiveness of HI-ZAC oral rinse in reducing oral malodor．[Patients and Methods] The study population included seven patients whose volatile sulfur compound (VSC) levels exceeded the reference values (hydrogen sulfide [H2S] >112 ppb or methyl mercaptan [CH3SH] >26ppb) at the first measurement using an Oral ChromaTM device. Patients were advised to omit their usual oral hygiene practice, and to not ingest any food or drink on the day of assessment. To evaluate the effects of tooth brushing in reducing oral malodor, the subjects' VSC levels were measured after tooth brushing (the second measurement). After the second measurement, the subjects rinsed their mouths with 5mL of HI-ZAC oral rinse；the VSC levels were measured immediately after rinsing (the third measurement) to evaluate the effects of HI-ZAC oral rinse on halitosis.[Results] The results showed that tooth brushing did not reduce the VSC levels to a statistically significant extent. A Friedman test followed by multiple comparison testing using a Wilcoxon signedrank test with Bonferroni correction was performed to evaluate the changes in VSC levels. This revealed significant changes in the H2S value from the first to third measurements (P<0.05) and from the second to third measurements (P<0.05), confirming that the HI-ZAC oral rinse was highly effective for reducing VSC levels. All of the subjects showed a CH3SH level of 0 ppb after rinsing with HI-ZAC oral rinse.[Conclusion] HI-ZAC oral rinse was therefore found to be useful for reducing halitosis.